HUBUNGAN ANTARA TEKANAN EKONOMI DAN MEKANISME KOPING DENGAN KESEJAHTERAAN KELUARGA WANITA PEMETIK TEH - Firdaus, Firdaus; Sunarti, Euis (Jurnal Ilmu Keluarga dan Konsumen, 2009)
Study in correlation between economic pressure and coping mechanism and its impact to family welfare in peasant in Indonesia are still less likely to be done. The general objective of this research was to analyze the correlation between economic pressure, financial management, and coping mechanism with family welfare of plantation women workers. This was cross sectional study that involved 87 families of plantation women workers who had under-6 years old children as samples. The data which was collected in April 2008 consists of primary and secondary data. The primary data consists of economic pressure, financial management, and coping mechanism that taken by using structured questionnaire. Result of the research shows that there are significant correlation between family size with economic pressure and between economic pressure with family welfare. It means that the bigger family size, then higher level economic pressure, and then lower the level of family welfare. There are positive significant correlation between education level with financial management and between financial management with family welfare. here are also negative significant correlation between sample’s age with subjective and objective economic pressure, and positive significant correlation between economic pressure with coping mechanism in reducing food and non-food expenditure.